Manajemen Lembaga Berbasis Islam: Manajemen Madrasah dan Pondok Pesantren di Pesantren Al Ma’had Al Islamy Al Ma’ruf Kudus - Miftah, Miftah; Baidi, Baidi (Empowerment: Jurnal Pengabdian pada Masyarakat, 2024)
This article wants to reveal how madrasas and Islamic boarding schools are managed in order to obtain high quality education. Management here is very necessary for an organization as big as Ma'had Al Islmay Al Ma'ruf Kudus to run as safely as it should. The management of madrasas and Islamic boarding schools cannot be haphazard because they must be competitive with other educational institutions and must produce Muslim scholars who are in accordance with their scientific discipline and are useful for the community. The system used in management must consist of four important elements, namely evaluation, calculation, management and leadership. Of course, when this is carried out properly, institutions as large as Islamic boarding schools or madrasas can be competitive and produce outputs that are considered by society which are inseparable from religious values ​​and have abilities that are superior to those of other modern humans. In this way, Islamic boarding schools and madrasas will produce leaders who are strong for the people in the future in accordance with the demands of the times.